2002
DOI: 10.1002/mrc.1083
|View full text |Cite
|
Sign up to set email alerts
|

NMR diffusion coefficient study of steroid–cyclodextrin inclusion complexes

Abstract: The complexes formed by the steroid rocuronium bromide with four different cyclodextrins (bcyclodextrin, g-cyclodextrin, Org 26054 and Org 25969) were investigated. The diffusion coefficients of the steroid-cyclodextrin complexes were 6-15% lower than those of the native cyclodextrins, consistent with a 1 : 1 stoichiometry for all of the complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 9 publications
(7 reference statements)
2
33
0
Order By: Relevance
“…The densities and particle sizes were taken to be those of a typical solid particulate material. Drug molecular weight was assumed to be 350 g/mol, and diffusivity was assumed to be 5.0EÀ6 cm 2 /s, a typical value for a small molecular weight drug molecule (Cameron and Fielding, 2002;Carrier et al, 2007). The properties of CD were taken to be those of b-CD (Cameron and Fielding, 2002); molecular weight and solubility were obtained from SciFinder 1 .…”
Section: Numerical Solution To the Ncpm Model Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The densities and particle sizes were taken to be those of a typical solid particulate material. Drug molecular weight was assumed to be 350 g/mol, and diffusivity was assumed to be 5.0EÀ6 cm 2 /s, a typical value for a small molecular weight drug molecule (Cameron and Fielding, 2002;Carrier et al, 2007). The properties of CD were taken to be those of b-CD (Cameron and Fielding, 2002); molecular weight and solubility were obtained from SciFinder 1 .…”
Section: Numerical Solution To the Ncpm Model Equationsmentioning
confidence: 99%
“…Drug molecular weight was assumed to be 350 g/mol, and diffusivity was assumed to be 5.0EÀ6 cm 2 /s, a typical value for a small molecular weight drug molecule (Cameron and Fielding, 2002;Carrier et al, 2007). The properties of CD were taken to be those of b-CD (Cameron and Fielding, 2002); molecular weight and solubility were obtained from SciFinder 1 . Other input parameters were assigned representative ''low'' and ''high'' values, including drug solubility, absorption constant, dose, binding constant, molar ratio of CD:drug; and the volume of the intestinal lumen.…”
Section: Numerical Solution To the Ncpm Model Equationsmentioning
confidence: 99%
“…Changes in relaxation times have also been measured [128,129], but the interpretation of the data is model dependent and less straightforward than data from self-diffusion measurements, which are conceptually easier and often nowadays experimentally easy to obtain. NMR diffusometry has been used to study inclusion complexes between cyclodextrin and different substrates [130][131][132][133]. The selfdiffusion measurements are in principle applicable to any systems as long as the free and complexed guests (please note that on account of the rapid exchange on the NMR time scale, average diffusion coefficients for both the guest and for the CD are obtained)…”
mentioning
confidence: 99%
“…[14] Receptor 4 was named dalexabe because this compound is made up of [ [17,18] in the presence of a molecule with similar size, daxacyan (which is well-known to not form a dimer), [15] confirmed that in diluted solutions receptor 4 stands as a monomer, as the diffusion coefficients differed by less than 10 %.…”
Section: Resultsmentioning
confidence: 94%